Mixed Security Testing of Alternative Portfolio Selection Models - Alexander, Gordon J. (Journal of Financial and Quantitative Analysis, 1977)
The general framework employed in analyzing diversification among securities involves the mean-variance theory of portfolio selection described by Markowitz [8]. Observation of the securities comprising the efficient set indicates which financial sssets possess attributes (i.e., expected return and covariances) making them worthwhile components of an optimally diversified portfolio. This paper will be concerned with forming an efficient set from four security classes—common stocks, preferred stocks, corporate bonds, and U.S. government bonds (hereafter denoted CS, PS, CB, and GB, respectively). The first objective will be to derive and analyze an efficient set from a sample of these securities in order to determine which securities have potential benefits for diversification.